Poster Session: Modeling sensitivity to red and green small spots: The effect of cone topography and spectral sensitivity - Greene, Maxwell J.; Pandiyan, Vimal P.; Sabesan, Ramkumar; Tuten, William S. (Journal of vision (Charlottesville, Va.), 2025)
To understand how well sensitivity to small chromatic flashes is explained simply by cone activity, we compared thresholds to 543 nm ("green") or 680 nm ("red") incremental flashes with theoretical predictions. Thresholds were measured in two color-normal males for stimuli presented at ~2 deg eccentricity on an achromatic background through an adaptive optics platform. Stimuli subtended 2.25 arcminutes, were 67 ms in duration, and were stabilized on the retina. A strong, positive correlation between red sensitivity (normalized by green sensitivity) and the proportion of stimulated receptors classified as L-cones by optoretinography was found. Theoretical predictions of red and green thresholds were derived from two models. In the first model, sensitivity was assumed to depend only on the cone spectral sensitivities, scaled by the numbers of L and M-cones illuminated by the stimulus. In the second model, thresholds were computed based on cone isomerizations for ideal observers possessing the subjects' actual cone mosaics. Both models account for much of the variance in the empirical data. For either model, residuals approach their minima when distinct, physiologically-plausible L-cone spectra (separated by 4.5 nm) are assumed for each subject. This suggests intersubject variation in L-cone photopigments. We intend to verify this potential variation by sequencing each subject's cone opsins.